Facilitators and Barriers to Living with Psychosis: An Exploratory Collaborative Study of the Perspectives of Mental Health Service Users. (September 2013) - Makdisi, Lana; Blank, Alison; Bryant, Wendy; Andrews, Christine; Franco, Lucia; Parsonage, Jackie
Introduction: The purpose of this research was to deepen understanding of what is helpful to those who have experienced psychosis, in order to facilitate best practice within mental health services. Psychosis presents challenges for people on an everyday basis, yet strategies can be developed to facilitate living with psychosis. Investigating the service user's perspective is crucial for informing recovery oriented occupational therapy practice. Method: Initiated and designed by a service user research group, this research was exploratory and, primarily, participatory. Data were gathered from two focus groups, involving 13 people with experience of psychosis, facilitated by service user researchers and an MSc student. Data analysis was systematic and based on grounded theory principles Findings: Participants shared experiences and thoughts about their everyday lives. Data analysis revealed six elements of the self: the social self; the occupational self; the integrated self; the unsupported self; the stigmatised self and the isolated self. The importance of balancing these six facets of the self is theorised as being essential to successfully managing the experience of living with psychosis. Conclusion: This emergent theory could underpin occupation-focused approaches to living with psychosis, with interventions aimed at enabling service users to balance the experience of psychosis with satisfying and contributing lives or recovery.